Comparison of differential and integral methods for coal oxidation kinetic analysis; Journal of Physics: Conference Series; Vol. 1128 : Thermophysics and Physical Hydrodynamics - Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich; Gubin V. E. Vladimir Evgenievich; Gvozdyakov D. V. Dmitry Vasilievich; Tolokolnikov A. A. Anton Andreevich (2018, 2018)
Title screen